Multigram synthesis of an orthogonally-protected pentasaccharide for use as a glycan precursor in a Shigella flexneri 3a conjugate vaccine: application to a ready-for-conjugation decasaccharide. Issue 22 (23rd September 2021) - Cornil, Johan; Hu, Zhaoyu; Bouchet, Marion; Mulard, Laurence A.
Abstract : Fine-tuned catalytic processes facilitating regio- and stereoselective conversions for the large-scale synthesis of a pentasaccharide and its oligomerization into ready-for-conjugation haptens. Abstract : The rapidly growing interest in carbohydrate-based bioactive molecules calls for strategies enabling the appropriate design and large-scale delivery of the glycan moiety. Herein, we describe the robust and high-yielding chemical synthesis of an orthogonally-protected pentasaccharide intended for use as a central building block in vaccine development against Shigella flexneri 3a. Elaborated from advanced crystalline intermediates and fine-tuned catalytic processes facilitating regio- and stereoselective conversions, a robust [2 + 3] strategy was designed, which avoided several tedious purifications and efficiently delivered multigram amounts of the target pentasaccharide. Conversion of this intermediate into a donor and a linker-equipped acceptor then merging then into the frame of a [5 + 5] glycosylation step furnished a decasaccharide encompassing one trichloroacetamide moiety per repeat. Chemoselective delevulination and subsequent Pd(OH)2 -mediated hydrogenolysis enabling concomitant hydrodechlorination and azide reduction gave the ready-for-conjugation dimer of the repeating unit of the O-antigen from S. flexneri 3a featuring the natural stoichiometric O -acetylation. The proof-of-concept was established, opening the way to larger S. flexneri 3a oligosaccharides and fine-tuned glycoconjugates.